Mechanical Properties and Mechanism Analysis of Magnetorheological Shear Thickening Colloid. Issue 1 (1st March 2022) - Fu, Yankai; Du, Chengbin
Abstract: Magnetorheological shear thickening material is a new type of composite material, which has both magnetorheological properties and shear thickening properties.In this paper, the influence of two important factors to the magnetorheological properties and shear thickening properties have been studied. The factors includ boric acid status and the ratio of polydimethylsiloxane to post-treatment boric acid in the material fabrication process .The article also systematically analyzed the action mechanism of the magnetorheological shear thickening material, mainly explained the internal mechanism of cycle that the material changes from the initial chaotic state to the formation of a three-dimensional micro-magnetic particle chain network, and then returns to the initial state. The study of material preparation parameters provides an experiment basis which can provide parameter for the preparation of materials with specified properties.The clarification of the material mechanism provides an idea for the subsequent quantitative analysis of the action of carbonyl iron particles in the material under the three force systems, and provides a theoretical basis for the subsequent study of the material's kinetic model.